2013
DOI: 10.1039/c3cc40491a
|View full text |Cite
|
Sign up to set email alerts
|

Maltoheptaose promotes nanoparticle internalization by Escherichia coli

Abstract: Nanoparticles conjugated with D-maltoheptaose (G7) showed a striking increase in the internalization by Escherichia coli. This applies to strains with and without the maltodextrin transport channel and particles ranging from a few to a hundred nanometers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 38 publications
0
64
0
Order By: Relevance
“…7) [45,46]. On irradiation with UV light, the azide group is transformed into a highly reactive nitrene functionality that can insert into CH and NH bonds.…”
Section: Covalent Functionalization With Carbohydratesmentioning
confidence: 99%
“…7) [45,46]. On irradiation with UV light, the azide group is transformed into a highly reactive nitrene functionality that can insert into CH and NH bonds.…”
Section: Covalent Functionalization With Carbohydratesmentioning
confidence: 99%
“…Bacterial imaging has thus been demonstrated in several examples, either using the optical properties of the nanomaterial cores themselves, such as quantum dots and crosslinked polydiacetylene, [56,87,101] or by introducing fluorescent labels in the materials. [42,85,94,96] Furthermore, magnetic nanoparticles enable the use of magnetic resonance imaging.…”
Section: Glyconanomaterialsmentioning
confidence: 99%
“…[115118] Uptake of functionalized nanoparticles of core sizes <6 nm have also been proposed. [87,119,120] For example, Nadeau and coworkers reported that adenine- and AMP-conjugated CdSe and CdSe/ZnS quantum dots were internalized in B. subtilis and E. coli , presumably through purine-dependent mechanisms. [120] Furthermore, Yan and coworkers showed that maltoheptaose-functionalized magnetic iron oxide nanoparticles appeared to be internalized in E. coli , also suggesting that translocation through the inner membrane is a major barrier.…”
Section: Glyconanomaterialsmentioning
confidence: 99%
“…The plates were incubated at 37°C for 16-18 h. A resazurin solution (10 or 20 μL of 0.01 w/vol % to wells with 100 or 200 μL drug/bacteria mixture, respectively) was added to each sample, and the plates were incubated for 2 more hours, whereafter the color change was noted. The MICs obtained by color change corresponded to those from turbidity measurement (47), except where free drug precipitated. For extrapolation of partial growth inhibition by Gompertz function (48), the turbidity was recorded.…”
Section: -90 25mentioning
confidence: 99%
“…MIC Assays. MIC was determined by broth microdilution (46,47), with slight modifications. Liquid cultures of bacteria (E. coli ATCC 25922, E. coli ORN 178, E. coli ORN 208) were grown in log phase and diluted to 10 6 cfu/mL The aqueous nanoaggregates suspension was diluted sequentially with water.…”
Section: -90 25mentioning
confidence: 99%